2021
DOI: 10.3390/vaccines9010062
|View full text |Cite
|
Sign up to set email alerts
|

Change of Willingness to Accept COVID-19 Vaccine and Reasons of Vaccine Hesitancy of Working People at Different Waves of Local Epidemic in Hong Kong, China: Repeated Cross-Sectional Surveys

Abstract: Vaccine hesitancy is among the major threats to the effectiveness of vaccination programmes. This study aimed to report the trend in response to willingness to accept the COVID-19 vaccine between two waves of the local epidemic and examine differences among occupations. Two cross-sectional surveys were conducted online during the first wave (February) and third wave (August to September) of the local epidemic in 2020. Acceptance of the COVID-19 vaccine was measured along with personal protection behaviours and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
241
10
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 232 publications
(287 citation statements)
references
References 39 publications
34
241
10
2
Order By: Relevance
“…Internationally, preliminary evidence suggests that while vaccine hesitancy initially decreased in the early stages of the pandemic (Caserotti et al 2021), it has been on the rise in a number of countries throughout the world, even those experiencing high rates of COVID-19, and those under lock-down conditions. For example, Wang et al (2021) found that vaccine acceptance in Hong Kong was lower during their third COVID-19 wave, compared to the first, and research by Hacquin et al (2020) suggests that vaccine refusal steadily rose between May and September in France, with only 23% of survey participants being willing to take a future vaccine as reported in September 2020. Similarly, findings from the United States indicate that there was a steady increase in vaccine hesitancy throughout 2020 (Firdman et al 2020; Huynh 2020; Daly & Robinson 2020), however recent research by Pew Research Center (2020) suggests that this trend might be starting to change, with 60% of Americans reporting that would get a vaccine for COVID-19 in November 2020, up from 51% in September.…”
Section: International Evidence On Vaccine Hesitancymentioning
confidence: 99%
See 1 more Smart Citation
“…Internationally, preliminary evidence suggests that while vaccine hesitancy initially decreased in the early stages of the pandemic (Caserotti et al 2021), it has been on the rise in a number of countries throughout the world, even those experiencing high rates of COVID-19, and those under lock-down conditions. For example, Wang et al (2021) found that vaccine acceptance in Hong Kong was lower during their third COVID-19 wave, compared to the first, and research by Hacquin et al (2020) suggests that vaccine refusal steadily rose between May and September in France, with only 23% of survey participants being willing to take a future vaccine as reported in September 2020. Similarly, findings from the United States indicate that there was a steady increase in vaccine hesitancy throughout 2020 (Firdman et al 2020; Huynh 2020; Daly & Robinson 2020), however recent research by Pew Research Center (2020) suggests that this trend might be starting to change, with 60% of Americans reporting that would get a vaccine for COVID-19 in November 2020, up from 51% in September.…”
Section: International Evidence On Vaccine Hesitancymentioning
confidence: 99%
“…The fact that vaccine hesitancy appears to be rising in countries heavily affected by COVID-19 contradicts previous research which suggests that the increased risk of a disease should result in improvements to vaccine acceptance (Fridman et al 2020). Potential explanations for a rising trend in vaccine hesitancy include greater safety concerns and a perceived rush of vaccine development (Daly et al 2020; Huynh 2020; Wang et al 2021), a lack of trust in government and pharmaceutical industries, and perceptions that the vaccine isn’t effective (Hacquin et al 2020).…”
Section: International Evidence On Vaccine Hesitancymentioning
confidence: 99%
“…International surveys have shown that 28% of the general population are COVID-19 vaccine hesitant, with the highest rates in the 25-34 age group and in females [9]. Hesitancy reasons include concerns about safety, lack of effectiveness, and the belief that vaccination is unnecessary [10]. Twenty-nine percent of health care works are hesitant, with higher levels in young adults and females, and 41% of those hesitant have safety concerns about the vaccine [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that age, gender, race, education level, influenza vaccination status, and fear of COVID-19 transmission are associated with the willingness to get the COVID-19 vaccine. [14][15][16][17][18] In Japan, willingness to get the COVID-19 vaccine was previously examined in a single study of 1,100 adults, with results showing that vaccine hesitancy was higher in Japan than in other countries, particularly among women. 19 However, gender differences in the determinants of willingness to get the COVID-19 vaccine, such as demographic and health characteristics, influenza vaccination status, and fear of COVID-19 transmission, have not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%